Reframing Educational Priorities: A Philosophical Synthesis of Islamic and Critical Pedagogy - Mohammad Muslih; syarifah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study critically examines the hierarchy of educational elements—material (māddah), method (ṭarīqah), teacher (al-mudarris), and the spirit of the teacher (rūḥ al-mudarris)—from the perspectives of Islamic educational thought and critical pedagogy. Employing a qualitative philosophical literature review, the study synthesizes classical Islamic educational texts, contemporary works on fiqh al-awlawiyyāt, and recent empirical and theoretical literature in critical and humanistic pedagogy (2020–2025). Data were analyzed through thematic and philosophical-analytical procedures to map hierarchical relations among educational elements and to interpret the normative concept of ahammu as a principle of priority rather than negation. The analysis demonstrates that rūḥ al-mudarris constitutes the apex of the educational hierarchy, functioning as an ethical-spiritual habitus that governs pedagogical decision-making regarding materials, methods, and teacher competence. Grounded in fiqh al-awlawiyyāt, the study argues that educational effectiveness depends on the sequential fulfillment of prior elements, culminating in the cultivation of the teacher’s moral-spiritual orientation. This framework challenges technocratic and method-centered reforms by re-centering education as a value-laden praxis. The study’s primary contribution lies in offering a theoretically integrated model that bridges Islamic jurisprudential reasoning and critical pedagogy, positioning the spirit of teaching as a central analytic category in educational theory. The findings have significant implications for educational policy, teacher education, and curriculum development, particularly in contexts seeking to balance technical competence with ethical and spiritual formation.